Turbine blade tip aero-thermal management: Some recent advances and research outlook - Zhang, Q; He, L (Global Power and Propulsion Society, 2017)
This article provides an overview of some recent progress in understanding HP turbine blade shroudless tip heat transfer and aerodynamics, especially in a transonic regime. The review is mostly based on the experimental and numerical efforts the authors have been involved in during the past ten years. Some fundamental flow physics especially in high speed Over-TipLeakage (OTL) flows are highlighted, including tip choking, shock waves, and the roles played by flow turbulence, etc. These mechanisms bring qualitative differences in tip heat transfer and loss generation, and prospects in tip aerothermal management and control. Of great interest is the strong OTL flow–coolant interaction, which can dramatically affect the tip aerodynamics, and thus would challenge any “optimized” tip geometry based on an uncooled configuration. It is suggested that optimal tip aero-thermal configurations should be an iterative process between blade tip shaping and cooling injection scheme. Combining tip geometry shaping and cooling injection patterns concurrently may provide more extensive exploitation of tip aerothermal design space.